The use of low temperature nuclear orientation in the study of site distribution of implanted ions - Stone, N (Baltzer Science Publishers, Baarn/Kluwer Academic Publishers, 1994)
A brief introduction is given to the basic ideas of ion implantation and the methods of nuclear orientation and NMR on oriented nuclei. This outline review discusses experiments carried out using these methods to describe the lattice sites and hyperfine interactions of ions which have no equilibrium solubility in iron, when introduced into the iron lattice by implantation. Examples are given of substitutional and vacancy associated sites. The paper ends with a discussion of two problematic systems, Cs Fe and Fr Fe, under current investigation. © 1994 J.C. Baltzer AG, Science Publishers.